Standard Thermodynamic Properties, Biosynthesis Rates, and the Driving Force of Growth of Five Agricultural Plants - Popovic, Marko; Minceva, Mirjana (Frontiers in Plant Science, 2021)
Elemental composition of Gossypium hirsutum L. (cotton), Oryza sativa L. (Asian rice), Phaseolus vulgaris L. (common bean), Saccharurn spp. L. (sugarcane) and Zea mays L. (corn) was used to calculate their empirical formulas (unit carbon formulas) and growth stoichiometry. The empirical formulas were used to find standard enthalpy of formation, standard molar entropy, standard Gibbs energy of formation and standard molar heat capacity. A comparison was made between thermodynamic properties of live matter of the analyzed plants and other unicellular and multicellular organisms. Moreover, the growth process was analyzed through standard enthalpy, entropy and Gibbs energy of biosynthesis. The average standard Gibbs energy of biosynthesis was found to be +463.0 kJ/C-mol. Thus, photosynthesis provides energy and carbon for plant growth. The average intercepted photosynthetic energy was found to be 15.5 MJ/C-mol for the analyzed plants. However, due to inefficiency a great fraction of the intercepted photosynthetic energy cannot be used by plants. The average usable photosynthetic energy was found to be -2.3 MJ/C-mol. The average thermodynamic driving force for growth is -1.9 MJ/C-mol. Driving forces of growth of C3 and C4 plants were compared. It was found that C4 plants have a greater driving force of growth than C3 plants, which reflects the greater efficiency of C4 photosynthesis. The relationship between the driving force and growth rates was analyzed, by determining phenomenological L coefficients. The determined phenomenological coefficients span two orders of magnitude, depending on plant species and environmental conditions. The L coefficient of P. vulgaris was found to be lower than that of other plants, due to additional energy requirements of nitrogen fixation.